Straits settlements Blue Book miscellanea (imports/exports) 1886-1888 vol. 22-26 (Great Britain : Public Record Office, 1971)
Mengandungi'Blue Book for the year 1887-88';'Report on the Blue Book for 1887';'Appendix for the year 1886-87'.